Program Bantuan Pemerintah Dalam Pengelolaan Biaya Pendidikan Bagi Masyarakat Kurang Mampu - Munawwarah; Zubaidah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Management of education costs for underprivileged communities is a hot issue to be discussed, because it cannot be denied that there are many problems in the field related to education financing, such as the high cost of education causing many Indonesians to drop out of school, not to mention the various bad behavior of school officials, such as school principal who deliberately corrupts education funds. The aim of this research is to explain local government policies in managing education costs for underprivileged communities, especially at the elementary school level. The writing method uses content analysis with a qualitative approach. Data collection techniques include reading literature sourced from books or articles that are relevant to the research. Meanwhile, data analysis techniques involve inventory, categorization and analysis of research data. The research results show that the government's policy in allocating educational funding resources to help all underprivileged students, especially at the elementary school level, has been pursued through several funding sources and programs that have been launched, such as the Poor Student Assistance (BSM) program, the Smart Indonesia Card (KIP) program. , and the Family Hope Program (PKH)